Answer:
The answer is terminating!
Step-by-step explanation:
repeating never ends
To find the inverse, interchange the variables and solve for y.
f^-1 (x) = 4 + x/2
Answer:
= 11/3
Step-by-step explanation:
1. COMBINE MULTIPLIED TERMS INTO A SINGLE FRACTION
- 7/3 (3x-2)= -21
-7 (3x-2) = -21
-----------------------
3
2. DISTRIBUTE
-7( 3x- 2) ➗ 3 =-21
3. MULTIPLY ALL TERMS BY THE SAME VALUE TO ELIMINATE FRACTION DENOMINATORS
-21x + 14 ➗ 3 = 3 (-21)
4. CANCEL MULTIPLIED TERMS THAT ARE IN THE DENOMINATOR
3 ( -21x + 14) ➗ 3 (-21)
5. MULIPLY THE NUMBERS
-21x + 14 = 3(-21)
6. SUBTRACT 14 FROM BOTH SIDES OF THE EQUATION
-21x + 14 = -63
7. SIMPLIFY
-21x = - 77
8. DIVIDE BOTH SIDES OF THE EQUATION BY THE SAME TERM
-21x/-21 = -77/-21
9. SIMPLIFY
x = 11/3
E-3 will be the first student to start writing the assignment.
It is clearly stated in the statement that the order of starting the assignment and the order of the completion of the assignment is not the same, the digit in the name of the executive is also not same. This information puts some restrictions.
E-1 can neither be the first one to start nor the first one to complete. Similarly, E-2 cannot be the second one and E-3 cannot be the third one.
It is given that the last student (the third one) to start is the first student (the first one) to complete. This can neither be E-3 nor E-1. It is E-2
The final arrangement is as follows.
Start Complete
First E-3 E-2
Second E-1 E-3
Third E-2 E-1
E-3 is the first one to start writing the assignment.
More similar problems are solved in the link.
brainly.com/question/28391619?referrer=searchResults
#SPJ4